Evaluating the safety and efficiency of day-care hysterectomy: a comparative study using propensity score matching - Cao, Qinyan; Liu, Tianjiao; Su, Yunyi; Wu, Xian; Xie, Aijie; Wang, Hui; Liu, Ying; Yu, Jie; Wu, Tenglan; Liao, Xiaoyan; Cheng, Wei; Liao, Jianmei; et al. (Frontiers in Medicine, 2025)
ObjectiveTo compare the outcomes of hysterectomy performed via traditional inpatient procedure versus day-care procedure with a focus on surgical time, post-operative recovery, costs, and patient satisfaction, using propensity score matching (PSM) to adjust for confounding variables.MethodsA total of 519 patients undergoing hysterectomy were initially identified. After PSM, 340 patients were included for analysis. Primary outcomes included perioperative complications, surgical time, post-operative discomfort, hospital stay, total cost, and patient satisfaction. Multiple linear regression analysis was performed to explore factors associated with operative bleeding and surgical time. Binary logistic regression was employed to analyze the factors influencing postoperative discomfort.ResultsAfter PSM, the day-care group demonstrated significantly lower hemoglobin decline, post-operative discomfort rates, hospital stay, and total cost, along with higher patient satisfaction (p < 0.05). Multivariate analysis showed a significant correlation between post-operative discomfort and both surgical modality and procedure time. For each additional minute of surgery time, the risk of post-operative discomfort increased by 2% (95% CI: 1.01, 1.03, p < 0.001). Furthermore, the ERAS-based day-care surgical modality reduced the risk of post-operative discomfort by 80% (95% CI: 0.08, 0.50, p < 0.001).ConclusionThe day-care procedure, guided by an enhanced recovery after surgery protocol, not only reduces hospital stay and overall costs but also improves patient satisfaction and reduces post-operative complications without compromising safety. These findings support the feasibility and benefits of day-care hysterectomy as a viable option for appropriately selected patients, offering significant advantages in terms of recovery and cost-efficiency.